THE EFFECT OF COMPLETE SENTENCE TYPE OF COOPERATIVE LEARNING MODEL TOWARDS STUDENTS’ COGNITIVE ON SOCIAL SCIENCE SUBJECT AT GRADE V OF PRIMARY SCHOOLS - Muhammad Faiz; Suparno; M. Taufik (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The background of this study was the students’ insufficient cognitive abilities. This research employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design to investigate the effect of the complete sentence learning model on grade V students’ cognitive learning outcomes in social science (IPS) at SDN Kebaharan 1 Kota Serang during the odd semester of the 2020/2021 academic year. The study focused on Theme 1: Animals and Human Organs of Motion, Subtheme 3: The Environment and Its Benefits, Learning 4. The samples were 60 students, with 30 in the experimental class (VB) and 30 in the control class (VA), selected through purposive sampling. Post-test results showed that the experimental class achieved an average score of 79.7, while the control class scored 71.9. This indicated that the complete sentence learning model was more effective than the concept sentence model, as it actively involved students in group discussions to complete incomplete paragraphs. The findings suggest that the complete sentence learning model can effectively enhance students’ cognitive abilities in social science learning.